Persepsi Masyarakat terhadap Penerapan Sharia Compliance Pada Bank Syariah di Kecamatan Barabai - Laila Martasari; Sepky Mardian (Jurnal Dinamika Akuntansi dan Bisnis, 2015)
Recently, the Islamic banking grew up significantly. In Barabai, many the Islamic banks has been established and operated. The study focused on the perception of Islamic society toward the sharia compliance practices in Barabai district. The objective is to highlight their perception on it based on the financial reporting, product, services, GCG and environment focus with 5 sharia compliance approach. The contract, maqashid sharia, halal-haram, documentation and financial reporting. The study involved the different society like the lecturer, student, state- owned employee, civil servant, trader, etc. as the respondents. The primary data’s are used by the questionnaire, while the secondary data’s are literature survey. The sample is consisting of 114 respondents with random sampling. The respondents are chosen by accidental sampling. The study found that the perception of the societies toward the sharia compliance practices in the Islamic banks in Barabai is neutral with the average score 3.39.